Influence of Drilling Along Pilot Holes on Drilling Performance and Effective Rock Strength - Abourawi Alwaar; Ibrahim Futhiez; Abdelsalam Abugharara; Yahui Zhang; Stephen Butt (Applied Sciences)
This study investigates the intricate relationship between bit rock interactions and drilling parameters for multiple-diameter hole drilling scenarios. Two sets of experiments were conducted in the Drilling Technology Laboratory at Memorial University of Newfoundland (DTL-MUN) using a fully instrumented Large-scale laboratory Drilling Simulator (LDS). The study contained two critical stages. Pre-coring operations using various diameter coring bits were completed to ensure thorough analysis. Next, drilling using a 5-cutter Polycrystalline Diamond Compact (PDC) bit with a larger diameter than all pre-cored holes, at constant Weight on Bit (WOB) and Revolution per Minute (RPM), was performed. The type of rock used in the experiments is a high-strength gabbro formation. Results indicate that pre-cored holes exhibited higher Rates of Penetration (ROP) than un-pre-cored holes, reflecting improved drilling performance and higher torque due to reduced bit–rock interaction area. A distinct relationship was observed between bit–rock interactions, torque, ROP, Mechanical Specific Energy (MSE), and applied WOB in multi-diameter drilling. ROP decreased as the pilot hole diameter decreased due to increased bit–rock interaction. The recorded data of WOB and the torque responses showed a decrease in amplitude as the bit–rock interface area increased, suggesting a positive interaction between drilling efficiency and downhole conditions. The modified Maurer model found a correlation between increased pilot hole diameter and decreased effective rock strength. These results highlight the significance of conducting a thorough drilling parameter analysis and the need for additional study to clarify the underlying mechanisms influencing drilling performance in multi-diameter hole drilling scenarios.